The Causality Between Agriculture, Industry, and Economic Growth: Evidence from Indonesia - Abdul Bashir; S. Suhel; A. Azwardi; Dirta Pratama Atiyatna; Ichsan Hamidi; Nazeli Adnan (Faculty of Economic and Business, 2019)
The industry is the current engine of the Indonesian economy over the past three decades; the economic structure in Indonesia has the transformation from the agriculture sector to the industry sector. The objective of this study is to examine the causality between agricultural, industry, and economic growth in Indonesia. By using the vector error correction model (VECM), this research finds that in the long-term, there is directional causality from the industry added value, economic growth on the agricultural added value. Meanwhile, in the short-term, the variable of industry added value and economic growth has the two-way causality. Besides, the agricultural added value can only affect the industrial added value and economic growth in the short-term. These findings support the idea that the agricultural sector plays a vital role in the economy, such as increasing economic growth and growth in other sectors, especially the industrial sector in this case.JEL Classification: F40, L60, O13, O47